The role of marbling as an intrinsic characteristic at the point of meat purchase–the Taguchi approach. Issue 1 (October 2021) - Rajic, S; Djordjevic, V; Baltic, T; Simunovic, S
Abstract: Meat quality is considered a complex concept depending on many characteristics that could be intrinsic or extrinsic. At the same time, intrinsic and extrinsic quality cues affect consumers' purchasing decisions. The importance of each quality cue was analysed and discussed in previous literature. Thus, colour and level of marbling of fresh meat were defined as key quality cues at the point of meat purchase. These characteristics are mostly related to pork and beef. The aim of this study was to identify quality characteristics that most closely match the consumer's preferences and at the same time could be related to quality losses. For that purpose, this paper gives a novel approach of the potential application of Taguchi loss function associated with quality characteristics and related losses for colour and level of marbling. This application can be implemented by providing a quality characteristic's proper target values and limits, which would make the meat production process more consistent.